Biosimilars of filgrastim in autologous stem cell transplant: reduction in granulocyte-colony stimulating factor costs, but similar effects on bone marrow recovery. Issue 1 (January 2014) - Ianotto, Jean-Christophe; Ngo Sack, Françoise; Couturier, Marie-Anne; Tempescul, Adrian; Mugnier, Nathalie; Delepine, Pascal; Guillerm, Gaelle; Berthou, Christian
Abstract Granulocyte-colony stimulating factors (G-CSFs) enhance bone marrow (BM) recovery after autologous stem cell transplant (ASCT) in patients with lymphoma and myeloma. Few publications exist that discuss the use of filgrastim biosimilars after ASCT. We conducted a single-center retrospective study in patients with lymphoma and myeloma treated at Brest Hospital to assess the cost reductions related to and the efficiency and safety of filgrastim biosimilars. We identified 65 patients with lymphoma or myeloma treated with filgrastim biosimilars for ASCT and compared 19 parameters of these patients, including BM recovery, side effects, infectious complications and treatment costs, with published historical data on a cohort of 50 patients treated with classic filgrastim. We observed a significant reduction of G-CSF costs in both groups but did not observe a change in total hospitalization costs (representing less than 2% of the costs) between groups. Additionally, we did not observe differences between the two groups in BM recovery, infectious complications, side effects or the other studied parameters. In this retrospective study, the absence of differences between groups after ASCT in lymphoma and myeloma led us to believe that these drugs could be safely and effectively used for such indications without a significant impact on hospitalization costs. A prospective study should be conducted to confirm our results.